Qualitative Research on Female Boards IT Investment Decisions in A Males Homogeny Environments - Witra, Widyasari Puspa Permata; Subriadi, Apol Pribadi (Sistemasi: Jurnal Sistem Informasi, 2023)
The primary purpose of this paper is to investigate the level of IT decisions accuracy between female and male directors on board. The research uses qualitative studies by interviewing four directors (two females and two males) who are in charge of making IT investment decisions. Furthermore, the data analysis uses Leadership Theory, Decision Quality Theory and Analytic Hierarchical Process. Results show that gender plays a pivotal role in shaping board directors' conduct in an IT investment decision-making where male and female leaders have specific attributes that will contribute to a successful IT investment decision-making. Moreover, the results also can be used as a fundamental for enterprises to change their policy regarding gender equality in a workplace to create a more diverse working environment. This research becomes significant considering the number of females on IT and board remains limited for several years despite women emancipation being encouraged across many platforms.